Incidencia de la acumulación de envases de polietileno de alta densidad (hdpe) en la contaminación ambiental de la ciudad de Latacunga, durante el período 2015 - 2016 - Moreno Corrales, Fabián Vladimir (2016)
The present research about impact of the high density polyethylene (HDPE) plastic container accumulation in the environmental pollution of the Latacunga city, was development by application methods of environmental impact assessment, the results was obtained from surveys applied to the population about the topic pollution and data analysis on the amount generated plastic containers in the city which is estimated at 665,4 ton per year, in a certain way corroborating the existence environmental problem pollution because of this plastic, it is originated when doesn’t exist a suitable process after used it . In the proposal is showed the production process of recovering high density polyethylene (HDPE) plastic container through the selection, cleaning….